PEMBERDAYAAN UMKM BIJI KOPI ARABIKA DI DESA KADUWULUNG, SUMEDANG DALAM RANGKA MEMASUKI PASAR EKSPOR - Nora Nahdia Imania; Muhammad Indrawan Jatmika (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2023)
MSME is one type of business that has a big impact on the Indonesian economy. For this reason, empowering MSMEs will have a positive effect on advancing the economy. In line with this, the community service team conducted empowerment with the provision of insights gained through the Export School Internship and Independent Study programs. The community service team identified the problems encountered by conducting a field survey method and discussing with MSME business owners roasted Arabica coffee beans in Kaduwulung, Sumedang, West Java. After finding existing problems, the community service team provided empowerment by rebranding product packaging to improve brand image and adjustments to export standards, providing assistance in market analysis on the trademap.org website, assistance in creating promotional content on social media in the form of posters with adding a slogan that calls on the audience to get to know the brand better, as well as assistance in entering global market access by onboarding the global marketplace in a marketplace managed by an export school, namely the Depo Ekspor.